The Relationship of the Health Belief Model to the Prevention Behavior of Metabolic Syndrome: A Meta-Analysis Study - Cendekia Airedeta Mulianda; Dena Tri Solehaini (Journal of Health Promotion and Behavior, 2022)
Background: Risk factors for Metabolic Syndrome include hypertension, glucose intolerance, central obesity and dyslipidemia. These conditions if they occur together are referred to as Metabolic Syndrome which can increase the risk of non-communicable diseases, namely heart, stroke, and type 2 diabetes. This study aimed to estimated the relationship between the constructs of the Health Belief Model (HBM) on the prevention of metabolic syndrome (SM) risk factors.Subjects and Method: This article was compiled with a systematic review and meta-analysis study. This study uses the PICO Model. The meta-analysis study was conducted by searching for articles from databases in electronic form including Google Scholar, Pub-Med, and Science Direct. The keywords used are "Health Belief Model" or "Metabolic Syndrome Prevention" or "MetS" or "Risk Factors Metabolic Syndrome" or "Hypertension" or "High Blood Glucose" or "Insulin Resistance" or "Central Obesity" or "Dyslipidemia". The inclusion criteria for this study were full articles using a cross-sectional study, with the publication year 2012-2021. Analysis of articles in this study using RevMan 5.3 . software.Results: A total of 12 cross-sectional studies from Asia, and Africa were selected for systematic review and meta-analysis. The data collected showed that high perceived severity increases 1.38 times to metabolic syndrome risk factor prevention behavior compared with low perceived severity, but its statistically not significant (aOR= 1.38; 95% CI= 0.82 to 2.30; p= 0.220), high susceptibility perception increases metabolic syndrome risk factor prevention behavior 1.15 times compared  with low susceptibility perception (aOR= 1.15; 95% CI= 0.83 to 1.58; p= 0.410) but it was statistically not significant.Conclusion: Perceived severity, and susceptibility perception was not statistically significant in predicting preventive behavior for metabolic syndrome risk factors.Keywords: health belief model, risk factors, syndrome metabolic, meta-analysis Correspondence:Cendekia Airedeta Mulianda. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: c.airedeta@gmail.com. Mobile: +6282336712311.Journal of Health Promotion and Behavior (2022), 07(01): 28-41DOI: https://doi.org/10.26911/thejhpb.2021.07.01.04